Aspek Kinerja Keuangan Daerah yang Berdampak Pada Pembangunan Manusia di Daerah Pemekaran - Siregar, Helly Aroza (Akuntansi & Ekonomika, 2023)
Is it true that the implementation of fiscal decentralization through the expansion of regions can have a significant impact on development and improve the welfare of people in the regions? This study aims to analyze the influence of the government's financial performance after the division in influencing the Human Development Index as an indicator of successful development and community welfare in the regions. The research method was conducted by using multiple linear regression analysis that processed financial ratio data from the APBD Report of Kepulauan Meranti Regency from 2010 to 2022. The results showed that financial performance as measured by PAD Effectiveness, Capital Expenditure Ratio, PAD Growth, and Financial Independence has a significant effect on the Index of Human Development, while the Efficiency of Regional Expenditure has no effect.